2018
DOI: 10.1039/c7nr09656a
|View full text |Cite
|
Sign up to set email alerts
|

F-Doped carbon nano-onion films as scaffold for highly efficient and stable Li metal anodes: a novel laser direct-write process

Abstract: Li metal is the most promising choice for anode in high-energy rechargeable batteries, but the dendrite growth upon cycling leads to safety concerns and poor cycle life. Herein, we demonstrate a novel and scalable approach for direct writing of a thin layer of carbon nano-onions on copper substrate to stabilize the Li metal anode and prevent the dendrite growth. The F-doped carbon nano-onion film (F-CNOF) scaffold enables reversible electroplating for over 1500 hours (300 cycles) with a coulombic efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The first strategy is based on doping by heteroatoms during the formation of CNs, and the second strategy is connected to the post‐synthesis treatment of already‐formed CNs using different oxidizing or reducing agents. For this purpose, doping CNOs with N, B, F, O and S was performed …”
Section: Doping Of Cnos By Heteroatomsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first strategy is based on doping by heteroatoms during the formation of CNs, and the second strategy is connected to the post‐synthesis treatment of already‐formed CNs using different oxidizing or reducing agents. For this purpose, doping CNOs with N, B, F, O and S was performed …”
Section: Doping Of Cnos By Heteroatomsmentioning
confidence: 99%
“…Next, very interesting direct modification of the CNO nanostructures was performed by Puthusseri and coworkers . A scalable approach for direct laser writing of a thin layer of CNOs on copper substrate was reported.…”
Section: Doping Of Cnos By Heteroatomsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] To realize viable application of Li metal anodes, continuous effort has been made for years to understand the mechanism of Li deposition and tackle the formation of dendrites. [24][25][26][27][28][29] For examples, Guo et al reported that 3D Cu with a large number of charge centers and nucleation sites facilitate the formation of relatively even Li surface. [24][25][26][27][28][29] For examples, Guo et al reported that 3D Cu with a large number of charge centers and nucleation sites facilitate the formation of relatively even Li surface.…”
mentioning
confidence: 99%